Effect of chronic sleep restriction and aging on calcium signaling and apoptosis in the hippocampus of young and aged animals - Souza, Luciane de [UNIFESP] (2012)
Aging leads to progressive deterioration of physiological function and diminished responses to environmental stress. Organic and functional alterations are frequently observed in elderly subjects. Although chronic sleep loss is observed during senescence, little is known about the impact of insufficient sleep on cellular function in aging neurons. Disruption of neuronal calcium (Ca2+) signaling is related to impaired neuronal function and cell death. It has been hypothesized that sleep deprivation may compromise neuronal stability and induce cell death in young neurons; however, it is necessary to evaluate the impact of aging on this process. Therefore, the aim of this study was to evaluate the effects of chronic sleep restriction (CSR) on Ca2+ signaling and cell death in the hippocampus of young and aged animals. We found that glutamate and carbonyl cyanide-p-trifluoromethoxyphenylhydrazone (FCCP) induced a greater elevation in cytosolic Ca2+ ([Ca2+](c)) in hippocampal slices from aged rats subjected to CSR compared to age-matched controls. Interestingly, aged-matched controls showed a reduced Ca2+ response to glutamate and FCCP, relative to both CSR and control young animals. Apoptotic nuclei were observed in aged rats from both treatment groups; however, the profile of apoptotic nuclei in aged CSR rats was highly variable. Bax and Bc1-2 protein expression did not change with aging in the CSR groups. Our study indicates that aging promotes changes in Ca2+ signaling, which may also be affected by CSR. These age-dependent changes in Ca2+ signaling may increase cellular vulnerability during CSR and contribute to Ca2+ signaling dysregulation, which may ultimately induce cell death. (c) 2012 Elsevier Inc. All rights reserved.